PENGARUH LATIHAN MENGGUNAKAN RESISTANCE BAND TERHADAP DAYA TAHAN OTOT LENGAN ATLET DAYUNG JUNIOR JALUR RAJO BUJANG KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Abdul Hamidy Ramadhan; Hirja Hidayat; Oca Fernandes; Siti Maesaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study uses a quantitative research method with Quasi-experimental (Nonequivalent Control Group Design), this design is almost the same as the pre-test and post-test control group design, which means that this design has two groups that are selected and then given a pre-test to find out the initial state of whether there is a difference between the experimental group and the control group, the difference lies in the sampling that is not randomly selected. Based on leven's test for equality of variances, a value of F=3.505 with a value of sig.=0.072. Because the significance value (sig.) is greater than 0.05, it can be concluded that the variance of the two groups is homogeneous, so the results of the t-test are used in the first line (equal variances assumed). In the independent sample t-test, the value of t=1.321 was obtained, with df=28 and sig. (2-tailed)=0.197. This significance value was greater than 0.05, which means that there was no significant difference between the treatment group and the control group in the post-test results. In addition, the average difference between the two groups was 1,667 with a 95% confidence interval range of -919 to 4,252. Since this range includes a value of zero, it further reinforces that there is no significant difference between the two groups.